2021
DOI: 10.1111/tpj.15630
|View full text |Cite
|
Sign up to set email alerts
|

A systems‐biology approach identifies co‐expression modules in response to low phosphate supply in maize lines of different breeding history

Abstract: Plants cope with low phosphorus availability by adjusting growth and metabolism through transcriptomic and proteomic adaptations. We hypothesize that selected genotypes with distinct phosphorous (P) use efficiency covering the breeding history of European Flint heterotic pool provide a tool to reveal general and genotype-specific molecular responses to P limitation. We reconstructed protein and gene co-expression networks by weighted correlation network analysis and related these to phosphate deficiency-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…In fact, so far, there have only been reported metabolomics and/or transcriptomic and ionomic studies focused on selected subsets of accessions/cultivars displaying high or low tolerance to limiting Pi growth conditions. In general, these studies identified some significant correlations between gene co-expression modules, metabolites, and/or elements with plant performance traits under low Pi growth conditions, which inform on metabolic pathways and transcriptional programs and potential TF regulators underlying low Pi tolerance, functional validation is still missing for most candidates (Hajheidari et al 2022;Han et al 2022;He et al 2022;Luo et al 2019). Only in one GWAS study in maize, the information on Pi starvation-responsive metabolites and the significant correlation between specific metabolites and plant performance traits has been used to identify potential candidate causal genes underlying QTLs for these traits.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, so far, there have only been reported metabolomics and/or transcriptomic and ionomic studies focused on selected subsets of accessions/cultivars displaying high or low tolerance to limiting Pi growth conditions. In general, these studies identified some significant correlations between gene co-expression modules, metabolites, and/or elements with plant performance traits under low Pi growth conditions, which inform on metabolic pathways and transcriptional programs and potential TF regulators underlying low Pi tolerance, functional validation is still missing for most candidates (Hajheidari et al 2022;Han et al 2022;He et al 2022;Luo et al 2019). Only in one GWAS study in maize, the information on Pi starvation-responsive metabolites and the significant correlation between specific metabolites and plant performance traits has been used to identify potential candidate causal genes underlying QTLs for these traits.…”
Section: Discussionmentioning
confidence: 99%
“…In maize, two prominent co-expression modules obtained by WGCNA, which included proteins and genes related to sucrose biosynthesis, lipid metabolism, respiration, and RNA processing, were found to be positively correlated with root and shoot traits in the maize phosphate-starvation response [ 48 ]. Based on WGCNA analysis, we found that two co-expression network modules, MEcoal2 and MEblue, were positively correlated with root and shoot traits under LP stress.…”
Section: Discussionmentioning
confidence: 99%
“…Total protein was extracted in a urea thiourea environment (He et al ., 2021). Microsomal fraction isolation followed established protocols (Pertl et al ., 2001).…”
Section: Methodsmentioning
confidence: 99%